(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2014)
Although the incidence of Rheumatic Mitral Stenosis is grossly reduced in Indian subcontinent, it occupies a greater segment among heart diseases complicating pregnancy. A 25 years old lady, who was not known as a case of valvular heart disease, was admitted in a secondary level hospital for emergency lower segment caesarean section. The patient developed severe pulmonary oedema during operation which was managed successfully. DOI: http://dx.doi.org/10.3329/jafmc.v9i1.18741 Journal of Armed Forces Medical College Bangladesh Vol.9(1) 2013: 118-121